Improving sweetpotato virus diagnostics - International Potato Center (2014)
Genomes of virus species and strains infecting sweetpotato in East, Southern and West Africa have been determined by next generation sequencing. A new diagnostic tool to detect all sweetpotato viruses simultaneously has been developed and will be progressively improved.